Bot Monitoring Jaringan Pada BMT Mentari Lampung Timur Menggunakan Mikrotik Dan API Telegram - Arif Hidayat; Ismail Puji Saputra; Ari Bowo (Institut Bakti Nusantara, 2022)
Network notifications are very much needed by the network technical team. In addition, network notifications function to provide information to the technical team to find out the current condition of the server or router which is under the supervision of the technical team so that if the server is down, it can be handled quickly. The research method used is DIO Network Lifecycle. DIO Network Lifecycle is a network design method or commonly referred to as a network service life cycle designed to support network development. The research phase begins with design, implementation and operation. The research output produced is in the form of BOT monitoring of the BMT Mentari Lampung Timur network using Mikrotik and the Telegram API.